STRUCTURAL-SEMANTIC AND LINGUOCULTURAL REPRESENTATION OF GENDER STEREOTYPES IN ENGLISH, RUSSIAN AND UZBEK MEDIA DISCOURSE (International Conference on Education, Psychology and Humanities, 2026)
This article investigates the structural-semantic and linguocultural representation of gender stereotypes in English-language social media discourse from a comparative perspective. The study examines media texts published on popular social networking platforms, focusing on the linguistic means through which traditional and contemporary gender stereotypes are constructed and communicated. Particular attention is paid to lexical choices, evaluative vocabulary, modal constructions, and pragmatic strategies that shape representations of masculinity and femininity. The analysis demonstrates that social media simultaneously preserve traditional patriarchal gender models and promote emerging discourses of gender equality and individual self-realization.
Keywords: gender stereotypes; social media discourse; media linguistics; linguoculturology; structural-semantic analysis; discourse analysis; pragmatics; English language; digital communication; gender representation.